A New Model for Capturing the Spread of Computer Viruses on Complex-Networks - Chunming Zhang; Tianliang Feng; Yun Zhao; Guifeng Jiang (Discrete Dynamics in Nature and Society)
Based on complex network, this paper proposes a novel computer virus propagation model which is motivated by the traditional SEIRQ model. A systematic analysis of this new model shows that the virus-free equilibrium is globally asymptotically stable when its basic reproduction is less than one, and the viral equilibrium is globally attractive when the basic reproduction is greater than one. Some numerical simulations are finally given to illustrate the main results, implying that these results are applicable to depict the dynamics of virus propagation.